Vetiver Grass (Vetiveria zizanioides) - A Method of Vegetative Soil and Moisture Conservation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Vetiver Grass (Vetiveria zizanioides) - A Method of Vegetative Soil and Moisture Conservation This handbook has been prepared to support field workers and farmers to develop appropriate soil and moisture conservation systems. Vegetative systems have...